Association of triglyceride-glucose index with prognosis of COVID-19: A population-based study. Issue 8 (August 2022) - Chang, Yoonkyung; Jeon, Jimin; Song, Tae-Jin; Kim, Jinkwon
Abstract: Background: Triglyceride-glucose (TyG) index is a simple and reliable surrogate marker for insulin resistance. Epidemiology studies have shown that insulin resistance is a risk factor for various infectious diseases. We evaluated the prognostic value of TyG index measured before the COVID-19 infection in COVID-19 infected patients. Methods: From a nationwide COVID-19 cohort dataset in Korea, we included COVID-19 patients diagnosed between Jan and Jun 2020. Based on the nationwide health screening data between 2015 and 2018, TyG index was calculated as ln [triglyceride (mg/dL) × fasting glucose level (mg/dL)/2]. Primary outcome is development of severe complications of COVID-19 defined as composite of mechanical ventilation, intensive care unit care, high-flow oxygen therapy, and mortality within two months after the diagnosis of COVID-19. Results: This study included 3887 patients with COVID-19 confirmed by reverse transcription polymerase chain reaction. Mean ± standard deviation of TyG index was 8.54 ± 0.61. Severe complications of COVID-19 were noted in 289 (7.44%) patients. In the multivariate logistic regression, TyG index was positively associated with severe complications of COVID-19 (adjusted odds ratio: 1.42, 95% confidence interval [1.12–1.79]). Conclusions: In COVID-19 infected patients, high TyG index was associated with increased risk for severe complications. TyG index might be useful predictor for the severity of COVID-19 infection.